Gut microbiota-specific IgA+ B cells traffic to the CNS in active multiple sclerosis - Pröbstel, Anne-Katrin; Zhou, Xiaoyuan; Baumann, Ryan; Wischnewski, Sven; Kutza, Michael; Rojas, Olga L.; Sellrie, Katrin; Bischof, Antje; Kim, Kicheol; Ramesh, Akshaya; Dandekar, Ravi; Greenfield, Ariele L.; et al. (Science immunology, 2020)
Changes in gut microbiota composition and a diverse role of B cells have recently been implicated in multiple sclerosis (MS), a central nervous system (CNS) autoimmune disease. Immunoglobulin A (IgA) is a key regulator at the mucosal interface. However, whether gut microbiota shape IgA responses and what role IgA+ cells have in neuroinflammation are unknown. Here, we identify IgA-bound taxa in MS and show that IgA-producing cells specific for MS-associated taxa traffic to the inflamed CNS, resulting in a strong, compartmentalized IgA enrichment in active MS and other neuroinflammatory diseases. Unlike previously characterized polyreactive anti-commensal IgA responses, CNS IgA cross-reacts with surface structures on specific bacterial strains but not with brain tissue. These findings establish gut microbiota-specific IgA+ cells as a systemic mediator in MS and suggest a critical role of mucosal B cells during active neuroinflammation with broad implications for IgA as an informative biomarker and IgA-producing cells as an immune subset to harness for therapeutic interventions.
Online veröffentlicht: 13. November 2020
Im Titel ist das Pluszeichen hochgestellt
Gesehen am 29.05.2024